2019
DOI: 10.12775/trvs.2019.004
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq based SNP discovery in gluteus medius muscle of Polish Landrace pigs

Abstract: Background: Single nucleotide polymorphisms (SNPs) are the well-known molecular markers in genetics and breeding studies applied to veterinary sciences and livestock production. Advancement of next generation sequencing (NGS) provides a high-throughput means of potential putative SNP discovery. The aim of the study was to identify the putative genetic variants in gluteus medius muscle transcriptome of Polish Landrace pigs.Methods. RNA-seq based NGS experiment was performed on Polish Landrace pigs fed with omeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Related studies showed that consumption of PUFAs and other fatty acids diets were genetically regulated the growth performance and immune system in pigs [23]. Our mapping results identified a total of 25.3 million paired-end reads (13.5 million in high PUFAs and 11.8 million low PUFAs group) in the liver transcriptome of Polish Landrace pig, in comparison to 50.5 million paired-end reads (18 million in high PUFAs and 32.5 million low PUFAs group) in gluteus medius muscle transcriptome of Polish Landrace pig [24]. In an another study on the domestic Nero Siciliano male pig in Brazil [25], 346.8 million paired reads were identified and after QC check 99.03% of the reads were successfully mapped to the reference genome.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Related studies showed that consumption of PUFAs and other fatty acids diets were genetically regulated the growth performance and immune system in pigs [23]. Our mapping results identified a total of 25.3 million paired-end reads (13.5 million in high PUFAs and 11.8 million low PUFAs group) in the liver transcriptome of Polish Landrace pig, in comparison to 50.5 million paired-end reads (18 million in high PUFAs and 32.5 million low PUFAs group) in gluteus medius muscle transcriptome of Polish Landrace pig [24]. In an another study on the domestic Nero Siciliano male pig in Brazil [25], 346.8 million paired reads were identified and after QC check 99.03% of the reads were successfully mapped to the reference genome.…”
Section: Discussionmentioning
confidence: 84%
“…Finally, with regards to the same or alternative SNPs alleles encoding amino acids regions, 27141 synonymous cSNPs and 5989 non-synonymous cSNPs were identified in high PUFAs dietary group of liver transcriptome, in comparison to 18701 synonymous and 4389 non-synonymous cSNPs, respectively in gluteus medius muscle transcriptome [24]. Whereas, 15128 synonymous cSNPs and 3900 non-synonymous cSNPs were identified in the low PUFAs dietary groups liver transcriptome in comparison to 24491 synonymous and 5879 non-synonymous cSNPs, respectively in gluteus medius muscle transcriptome of Polish Landrace pigs [24].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations